The Crises of Oedipus. (2nd January 2023) - Goetzmann, Lutz
Abstract : This article describes the various crises of the Oedipus complex. In the beginning, I address the crisis of the first traumatic days when Oedipus was to be abandoned in the wilderness. This early breakdown takes place at what may be denoted as stage zero . During this first crisis, the defensive solution is an act of doubling, according to Quinodoz's dédoublement of the parental pair, accompanied by the defenses of splitting, foreclosure, and annihilation. Protected by these defenses, the child would be able to search for a solution to the neurotic part of the Oedipus complex. According to Freud's and Lacan's conception, these phases encompass the stages of the imaginary omnipotence, of the symbolic prohibition, and the symbolic reconciliation. The second crisis of Oedipus signifies therefore that the desire encounters the prohibition of the third (e.g., the father). I will show these stages in the 1967 film adaptation of Oedipus Rex and the life of its director, Pierre Paolo Pasolini. Against this background, the third crisis of Oedipus is considered: the impending ecological catastrophe.